If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -20 = -10 Reorder the terms: -20 + 2x = -10 Solving -20 + 2x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 2x = -10 + 20 Combine like terms: -20 + 20 = 0 0 + 2x = -10 + 20 2x = -10 + 20 Combine like terms: -10 + 20 = 10 2x = 10 Divide each side by '2'. x = 5 Simplifying x = 5
| 9=t+9 | | -5=b-6 | | n+1=-5 | | d-2=-10 | | -5-25=0 | | t-10=-19 | | 13=d+6 | | -1=d+9 | | -3+m=2 | | 6(x-8)=-8 | | m/6=-1 | | k-9=-8 | | 12=n+9 | | 2x-3=-2x+1 | | -3+d=-6 | | b/-6=-1 | | w+1=6 | | t/-6=-3 | | b-2=6 | | 5x/x | | d+8=14 | | p-4-6p=1 | | -2=k+9 | | 3=t+4 | | -16=x-9 | | 1=k-7 | | 5x/1x | | 1x/1x | | 1/1 | | 7y+2(y-6)=4(y+2)-2 | | 5k=-20 | | x+30=103 |